Rapid Detection of Bacterial Pustule Disease on Soybean Employing PCR Technique with Specific Primers - ANDI KHAERUNI; ANTONIUS SUWANTO; BUDI TJAHJONO; MEITY SURADJI SINAGA (HAYATI Journal of Biosciences, 2007)
A rapid polymerase chain reaction (PCR)-based procedure was developed for detection of Xanthomonas axonopodis pv. glycines, the causal agent of bacterial pustule disease on soybean. A set of primers was designed from partial sequence of the pathogenicity gene of X. axonopodis pv. glycines strain YR32. Specific PCR product of 490 base pairs was produced from strains of X. axonopodis pv. glycines originally from Indonesia as well as from Taiwan. No other pathovars and bacterial species among those tested showed amplification product under optimized PCR conditions. Shaking infected soybean leaves in phosphate buffer saline during six hours was proved to be an essential in order to increase cell number of the bacterial. The procedure was applicable and reliable for detecting of pathogens in infected plant materials. The procedure was proved to be more effective than that of conventional detection and could be of great help for monitoring of pustule bacterial disease in the soybean fields. Key words: Xanthomonas axonopodis pv. glycines, bacterial pustule disease, rapid detection, PCR, specific primer